2019
DOI: 10.1101/844951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noncoding regions underpin avian bill shape diversification at macroevolutionary scales

Abstract: AbstractRecent progress has been made in identifying genomic regions implicated in trait evolution on a microevolutionary scale in many species, but whether these are relevant over macroevolutionary time remains unclear. Here, we directly address this fundamental question using bird beak shape, a key evolutionary innovation linked to patterns of resource use, divergence and speciation, as a model trait. We integrate class-wide geometric-morphometric analyses with evolutionary s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 115 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…Our results are also consistent with studies of craniofacial genetics from diverse vertebrates; the prevailing model is that the genetic architecture of craniofacial variation is highly polygenic (Richmond et al . 2018; Yusuf et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also consistent with studies of craniofacial genetics from diverse vertebrates; the prevailing model is that the genetic architecture of craniofacial variation is highly polygenic (Richmond et al . 2018; Yusuf et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2019, 2020)). In contrast, there are few examples of pairing geometric morphometric shape analysis with genome-wide scans to identify the genetic architecture of avian craniofacial variation (but see (Yusuf et al . 2020)).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, theory and data have shown that divergence with gene flow is facilitated when selection for reduction of gene flow acts on a large part of the genome, rather than being dependent on selection on a few loci 14,15,42 . Such a situation is highly likely in the grosbeak-seedeater system as the traits under selection (bill size and shape, and body size) are well known to be under polygenic control 21,43,44 . This is supported by the relatively high level of unique polymorphisms in the grosbeak (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As phylogenetic relationships among meiruans move towards resolution (Section 2), comparative methods could be used to identify genomic targets, for example. [120,121] Such goals come with the caveat that convergent evolution may be predictable at some hierarchical levels of biological organization, but not at others, for example. [8,122]…”
Section: Towards Predicting the Evolution Of Crabsmentioning
confidence: 99%